Startups as sustainability transformers: A new empirically derived taxonomy and its policy implications - Yasmin Olteanu; Klaus Fichter (Business Strategy and the Environment, 2022)
For research as well as policymakers aiming at fostering multilevel transitions toward sustainability, there is a clear need to better understand the transformative role and relevance of startups as newcomers in the market. The existing typologies of sustainable entrepreneurship and green startups have been derived from theory and are conceptual or anecdotal in nature. The lack of validity and generalizability is a major research gap, as the existing typologies do not provide a sufficient basis for policy decisions on how to promote which type of entrepreneurship to effectively support specific transition policies. Against this backdrop, we investigate the research question: Does the transformation orientation differ among startups, and if so, how can they be clustered as basis for sustainability transition policy? Based on a sample of 1674 startups and cluster analysis, the paper makes three important contributions: First, we provide a differentiated perspective and empirical data on the transformation orientation of newcomers. Second, we provide an empirically founded taxonomy of the transformative orientation of startups and contribute to theory-building of transformative entrepreneurship. Third, we test the assumption inherent in most existing frameworks that there exists a high-potential subgroup of startups. Our results confirm the existence of a clearly distinguishable subgroup with a particularly high transformation orientation, which we label as "sustainability transformers." In terms of transition strategies, policymakers can build on our findings to adjust public funds and support programs in favor of specific subgroups such as sustainability transformers.
Keywords: 330; cluster analysis; multilevel transition; sustainable entrepreneurship; sustainable startup; transformation orientation; transformative entrepreneurship